1991
DOI: 10.1007/bf00233024
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Gossypium hirsutum and G. barbadense from shoot apex tissues for transformation

Abstract: A method of regenerating cotton plants from the shoot apical meristem of seedlings was developed for use with particle gun and Agrobacterium-mediated transformation. This method was developed to circumvent the problems of genotype restriction and chromosomal damage frequently encountered in cotton regeneration in tissue culture through somatic embryogenesis. In this procedure, the cells of the shoot meristem are targeted for transformation. Normal and fertile plants of Gossypium barbadense Pima S-6, and 19 cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 23 publications
3
37
0
1
Order By: Relevance
“…For any tissue culture study, the surface of explants must be fully sterilized. In previous research, different sterilization methods were used to sterilize delinted cotton seeds surface (Gould et al, 1991;Chen et al, 1987;Zhang, 1994). Delintedseeds were disinfected as describedabove and the disinfected seeds were then cultured on MS medium for 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For any tissue culture study, the surface of explants must be fully sterilized. In previous research, different sterilization methods were used to sterilize delinted cotton seeds surface (Gould et al, 1991;Chen et al, 1987;Zhang, 1994). Delintedseeds were disinfected as describedabove and the disinfected seeds were then cultured on MS medium for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration from the shoot apex was direct and simple. Theoretically, each excised apex should develop into a rooted plant; however, the yield of shoots in vitro from isolated apices depends on the incidence of contamination and rooting efficiency (Gould et al, 1991). In recent years, protocols involving proliferation of cotton shoots (Agrawal et al, 1997;Hemphill et al, 1998) have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of using the shoot apex for Agrobacterium-mediated gene transformation is a low incidence of tissue culture induced genetic changes, and a simple and direct development of transformed plants (Gould et al 1991). Recently the shoot apex method has been used successfully in Agrobacterium-mediated transformation of rice (Clement et al 2016), cucumber (Baskaran et al 2016), and broccoli (Ravanfar & Abdul Aziz 2015) (Table 1).…”
Section: Shoot Apex Methodsmentioning
confidence: 99%
“…Different scientists reported that MS basal medium directly regenerated the plants from inoculated shoots (Murashige and Skoog 1962 ;Shabde and Murashige 1977 ) . The same medium has been used to regenerate other crops such as Gossypium (Gould et al 1991a ) , maize (Gould et al 1991b ) and cereals (Hiei et al 1997 ) . Tissue culture is considered as an essential step for transformation of the majority of plant species, consequently higher priority is needed to establish research procedures that could reduce the somaclonal variation (Birch 1997 ) .…”
Section: Tissue Culturementioning
confidence: 99%